Design of an algorithm for automatic correction of position in the PCB-drilled process using computer vision techniques (2015)
An algorithm for position control in perforated "Through-Hole" process in manufacturing of Printed Circuit Board, is presented. This algorithm is capable of providing a mechanism for visual feedback to a Computer Numeric Control machine in such a way that can automatically, compensate, detect and correct possible errors in the position of the drilling tool, before and during the drilling process mentioned above. Experimental evaluation of the algorithm developed on a modified Computer Numeric Control machine of low cost and general purpose, included 105 samples chosen randomly, the detection position showed an accuracy of 0.4853±0. 202 mm. The results show that the measured error is suitable for the application and the needs of the industry of manufacture of Printed Circuit Board in circuit with elements "through-hole".